Activity and stability of alpha-chymotrypsin in biocompatible ionic liquids: enzyme refolding by triethyl ammonium acetate - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
In view the of wide scope of structural information of biomolecules in biocompatible ionic liquids (ILs) in various applications including chemical and biochemical, it is essential to study the productive preferential interactions between biological macromolecules and biocompatible ILs. We have therefore explored the stability and activity of alpha-chymotrypsin (CT) in the presence of five ILs from different families, such as triethyl ammonium acetate (TEAA), triethyl ammonium phosphate (TEAP) from ammonium salts, 1-benzyl-3-methylimidazolium chloride ([Bzmim][Cl]), 1-benzyl-3-methylimidazolium tetrafluoroborate ([Bzmim][BF(4)]) from imidazolium salts and tetra-butyl phosphonium bromide (TBPBr) from phosphonium families. Circular dichroism (CD) and UV-vis spectrophotometer experiments were used to study CT stabilization by ILs, related to the associated structural changes and enzyme activity studies, respectively. We observed that all ILs have a dominant contribution to the stabilization of CT. The stability and activity of CT depends on the structural arrangement of the ions of ILs. Our experimental results explicitly elucidate that more hydrophobic imidazolium and phosphonium cations carrying longer alkyl chains of ILs ([Bzmim][Cl], [Bzmim][BF(4)] and TBPBr) were weak stabilizers for CT, while small alkyl chain molecules of triethyl ammonium salts (TEAA and TEAP) are strong stabilizers and therefore more biocompatible for CT stability. Our CD and NMR measurements reveal that TEAA is a refolding additive for CT from a quenched thermal unfolded enzyme structure.